Timing and Spectrum of Neurological Complications After Flow Diverter Implantation for Intracranial Aneurysms - Charbonnier, Guillaume (Front Neurol, 2021)
Background and Purpose: The aim of this study was to characterize neurological complications after flow diverter (FD) treatment on a long follow-up cohort and identify predictive factors associated with these complications. Methods: This study was conducted on a monocentric cohort of patients treated for intracranial aneurysms by FD. Results: Between September 2008 and July 2018, 413 patients were treated for 514 aneurysms: 18% of the patients presented with at least one neurological complication during a median follow-up of 446 days (IQR 186–1,210). Sixty-one patients presented with ischemic complications, 13 with hemorrhagic ones and 10 with compressive processes. Among 89 neurological complications 64.5% were peri-operative (occurring within the 30 days following the procedure) and 35.5% were delayed after 1 month. Conclusions: Overall, neurological complications after FD implantation were overrepresented by cerebrovascular ischemic events occurring during the peri-operative period, but also in a delayed manner after 1 year. Long-term follow-up is relevant after aneurysm intervention using FD.